Synthesis of multiarm star copolymers based on polyglycerol cores with polylactide arms and their application as nanocarriers1. Issue 20 (6th March 2015) - Adeli, M.; Namazi, H.; Du, F.; Hönzke, S.; Hedtrich, S.; Keilitz, J.; Haag, R.
<x xml:space="preserve">Abstract</x> Hyperbranched polyglycerol (hPG) with two different molecular weights (hPG2400 and hPG8000) was used as a macroinitiator for the polymerization of lactide.